Pengaruh Gaya Kepemimpinan Terhadap Kinerja Penyidik Pada Kepolisian Resort Sikka - Viktor Eko Transilvanus; Yustina Olivia da Silva da Silva; Leonardus Tunga (Peneliti.net, 2021)
Reforms have brought changes to civil servants, including the police of the Republic of Indonesia. The purpose of this study was to find out the partial leadership style had a significant effect on Sikka Police investigators. In accordance with the formulation of the problem and research objectives, this research design uses descriptive research methods. Determination analysis results obtained a coefficient of determination (R2) of 0.567 which means that the three independent variables in this are able to explain the variations in the performance of the Sikka Police Investigator's performance of 48.90%. While the remaining 51.10% is explained by other variables that are not included in this research model.